MOTIVASI BELAJAR DAN FAKTOR-FAKTOR YANG BERPENGARUH: SEBUAH KAJIAN PADA INTERAKSI PEMBELAJARAN MAHASISWA - Irmalia Susi Anggraini (Universitas PGRI Madiun, 2011)
It has been theoretically approved that motivation has become the most dominant factor which influence students’ achievement. Motivation is the generator of the learning process; and it will be essential to know where the motivation comes from. This study concerns on factors which influence the learning motivation for the student of Economy Study Program, State University of Malang. Motivation is cited as the independent variable which is measured by: (1) possession of literatures; (2) frequency of questioning to lecturer; (3) punctuality in completing individual work; and (4) percentage of attendance. The dependent variables of motivation are intrinsic and extrinsic. The result of the analysis shows that: (1) the significant internal factors are intention and orientation in choosing the study program; and (2) the significant external factors are quality of lecturer, lectures content, instructional method, classroom circumference and library support.